2016
DOI: 10.1016/j.jtcvs.2015.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Are homografts superior to conventional prosthetic valves in the setting of infective endocarditis involving the aortic valve?

Abstract: No significant benefit to use of homografts was demonstrable with regard to resistance to reinfection in the setting of IE. The choice among prosthetic options should be based on technical and patient-specific factors. Lack of availability of homografts should not impede appropriate surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
126
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(145 citation statements)
references
References 26 publications
(33 reference statements)
5
126
0
Order By: Relevance
“…When simple valve replacement is required, choice of valve-mechanical or tissue prosthesis-should be based on normal criteria: age, life expectancy, comorbidities, and expected compliance with anticoagulation. For patients with invasive disease and destruction, reconstruction should depend on the involved valve, severity of destruction, and available options for cardiac reconstruction Several studies have suggested that use of an allograft in patients with aortic valve IE is associated with better survival and lower risk of relapse (no early phase of recurrent infection) (43)(44)(45)(46). Due to technical difficulty and lack of evidence of superior resistance to reinfection, many surgeons prefer other conduits for reconstruction (44).…”
Section: General Considerations and Recommendations For Choice Of Recmentioning
confidence: 99%
“…When simple valve replacement is required, choice of valve-mechanical or tissue prosthesis-should be based on normal criteria: age, life expectancy, comorbidities, and expected compliance with anticoagulation. For patients with invasive disease and destruction, reconstruction should depend on the involved valve, severity of destruction, and available options for cardiac reconstruction Several studies have suggested that use of an allograft in patients with aortic valve IE is associated with better survival and lower risk of relapse (no early phase of recurrent infection) (43)(44)(45)(46). Due to technical difficulty and lack of evidence of superior resistance to reinfection, many surgeons prefer other conduits for reconstruction (44).…”
Section: General Considerations and Recommendations For Choice Of Recmentioning
confidence: 99%
“…The mean age of patients receiving bioprosthetic valves calculated from six studies reporting mean age of patients (19,20,22,23,28,29) was 59.2 years old (95% CI: 58.2-60.1). The mean age of patients receiving mechanical valves was 52.1 years old (95% CI: 51.4-52.9).…”
Section: Resultsmentioning
confidence: 99%
“…The optimal prosthesis has been debated for decades in the treatment of PVE[25]. Because of the advantages of removing the abscess, larger valve area, anti-infective and anti-coagulation therapy, surgical dogma indicate that a homograft or allograft is more beneficial than a prosthetic valve in the infected field[26]. However, the structural degradation and complicated surgical methods have limited their application [9,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the structural degradation and complicated surgical methods have limited their application [9,27]. A prospective study [26] from the databases of 2 tertiary academic centers suggested no difference in the prognosis of homograft and prosthetic valves in patients with IE. Our study suggested that there was a statistically significant higher trend of relapse in the biological valve group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation